1996
DOI: 10.1159/000189029
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation and Skin Diseases: Review of the Literature and Results of a 5-Year Follow-Up of 285 Patients

Abstract: We present a review of the current literature on skin diseases in renal transplant recipients (RTR) and the results of a 5-year follow-up of 285 patients. Many skin diseases are only an aesthetic and functional cause for interest, but HPV infections and skin cancers are significantly more frequent in RTR than in immunocompetent subjects and can affect a patient’s prognosis. For this reason, we feel dermatological surveillance of RTR is necessary for early diagnosis and treatment of all high-risk lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…In the reports, which usually refer a wide spectrum of cutaneous manifestations, the frequency of dermatomycoses is extremely variable, ranging from 7 to 75%, probably because of diverse diagnostic criteria, different geographical, climatic, social, economic, hygienic conditions and variable duration of immunosuppression [5, 6, 7, 8, 9, 10, 11, 12, 13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reports, which usually refer a wide spectrum of cutaneous manifestations, the frequency of dermatomycoses is extremely variable, ranging from 7 to 75%, probably because of diverse diagnostic criteria, different geographical, climatic, social, economic, hygienic conditions and variable duration of immunosuppression [5, 6, 7, 8, 9, 10, 11, 12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Among fungal infections, PV is reported as the most frequent clinical finding (18–48%), particularly in hot and damp climates [5, 8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…In various studies from India, the prevalence of warts in renal transplant patients has been shown to vary from 8% to 55%. [ 2 3 4 5 6 7 8 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of fungal, viral, bacterial infections and non-melanoma skin cancer (Squamous cell carcinoma, Basal cell carcinoma), pre-cancerous lesions is quite high in the renal transplant recipients (RTRs) compared to the general population. [3][4][5] A good understanding of the possible risks associated with renal transplant and adverse effects of the drugs used and possible cutaneous manifestations post-transplant, helps us in proper counselling to the patients regarding the preventive measures, adherence to therapy and better understanding of the disease condition Most of the cutaneous manifestations observed in RTRs are a result of immunosuppression; some, however, are drug-specific adverse effects. 6…”
Section: Introductionmentioning
confidence: 99%